Mokshartham Jagaditha: Studi Etnografis Well-Being pada Warga Ashram Gandhi Etnis Bali - Batuadji, Kristianto; Subandi, M.A. (ANIMA Indonesian Psychological Journal, 2009)
The purpose of this research was to investigate the concept of well-being among the Balinese Gandhian and the processes needed to reach such condition. The participants were the Balinese Gandhian from the Gedong Gandhi Ashram and the Ashram Gandhi Puri. Ethnographic perspective and phenomenological approach were applied in this study. Results reveal mokshartham jagadhita as a Balinese indigenous concept of well-being, referring to the physical and psycho- spiritual well-being which consists of: suka tan mewali duka (non-dual happiness), shaantih (peace), and harmony. This condition can be reached by the fulfillment of the physical, social, and psycho- spiritual needs, which transforms the personality into the ideal state of sthita-pradnya. The search for meaning was also involved during the attainment of this state. The aforementioned process involves the cognitive, affective, behavioral, and transcendental dimensions. The concept of mokshartham jagaditha is compared with the Western concept of well-being as well as with other concepts from Eastern traditions. Tujuan penelitian ini adalah menemukan gambaran mengenai konsep well-being dalam perspektif warga Ashram Gandhi etnis Bali, sekaligus mengungkap proses pencapaian kondisi well- being tersebut. Partisipan penelitian ini adalah warga Gedong Gandhi Ashram dan warga Ashram Gandhi Puri etnis Bali. Penelitian ini menggunakan perspektif etnografi dan pendekatan fenomenologi. Hasil penelitian menunjukkan bahwa masyarakat Bali memiliki konsep indigeneous tentang well-being yang disebut mokshartham jagadhita. Konsep ini terdiri atas komponen suka tan mewali duka (kebahagiaan non-dual), shaantih (kedamaian), dan harmoni. Kondisi ini dapat dicapai melalui proses pemenuhan kebutuhan fisik, sosial, dan psikospiritual yang mengantarkan individu pada transformasi menuju kualitas kepribadian ideal yang disebut sthita-pradnya. Proses pemaknaan sangat berperan dalam pencapaian kondisi ini. Proses ini melibatkan ranah kognitif, afektif, behavioral, dan bawah sadar. Konsep mokshartham jagadhita juga dibandingkan dengan konsep- konsep lain mengenai well-being, baik dari perspektif Barat maupun dari tradisi-tradisi Timur yang lain.